Theoretical Determination of Structures of Terpenoids 18a-Oleanane and A-Neo-18a-oleanene - Djeradi, H.; Rahmouni, A.; Cheriti, A. (Asian Journal of Chemistry, 2013)
The purpose of this study was to determine which of the quantum chemistry methods PM3, HF and DFT/B3LYP evaluate more accurately the geometric parameters of two terpenoids 18a-oleanane (1) and A-neo-18a-oleanene (2). The theoretical results were compared to experimental data generated by X-ray diffraction. Compound 1, C32H52O3, crystallizes in space group C2 with a = 13.3520 (2), b = 6.54000 (10), c = 32.4439(5) Å,V = 2798.13(7) Å3 and Z = 4. The structure was refined to a final R = 0.027 for the structure factors observed with I ³ 3s(I). The second molecule 2, C30H46O2, crystallizes in the monoclinic space group with a = 13.2214 (4), b = 6.4962 (2), c = 29.8420(9) Å,V = 2558.00(13) Å3 and Z = 4. The structure was refined to a final R = 0.061 for the structure factors observed with I = 2s(I). A comparative study using ab initio calculation (HF/6-31G**), semi empirique (PM3) and DFT(B3LYP/6-31G**) shows a high correlation with the geometric data of X-ray diffraction. The difference between the calculated and experimental values is very insignificant.